The Effect of William's Flexion Exercise on Reducing the Intensity of Dysmenorrhea in Young Women at SMP Negeri 1 Sobang, Pandeglang Regency - Dini Purwandani; Nofa Anggraini (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Dysmenorrhea is a disorder characterized by lower abdominal pain that occurs during menstruation. Dysmenorrhea problems in young women if not addressed immediately can adversely affect adolescent productivity including learning activities. Data from the Pandeglang District Health Office in 2021 reported dysmenorrhea cases in adolescents of 62.4% of the 5,000 adolescents surveyed and 35% of them complained of limited activity due to dysmenorrhea. Method: The research method uses quasi-experiments with a pre-posttest one group design. Sample of this study was 20 young women in grades IX who experienced dysmenorrhea with sampling technique uses total sampling. Instruments use questionnaires. Bivariate analysis uses the paired t-test. Results: The average intensity of menstrual pain in young women before being given physical exercise William's Flexion Exercise technique is 5.70 and after being given physical exercise William's Flexion Exercise technique performed for ±7-10 minutes is 2.85. Statistical tests results showed that there was an effect of William's Flexion Exercise on reducing the intensity of menstrual pain (dysmenorrhea) in young women (p value = 0.000). Conclusion: The provision of physical exercise William's Flexion Exercise technique is effective in reducing the intensity of menstrual pain in young women at SMP Negeri 1 Sobang, Pandeglang Regency. We recommend that young women can learn the physical exercise of William's Flexion Exercise technique and diligently practice the physical exercise to be applied by themselves when experiencing menstrual pain.